DEVELOPING ENGLISH DIGITAL CONVERSATION MEDIA FOR SPEAKING ACTIVITIES BASED ON TASK-BASED LEARNING - Astry Iswara Citra; Anni Holila Pulungan; Maya Oktora (Universitas Negeri Medan, 2021)
DEVELOPING ENGLISH DIGITAL CONVERSATION MEDIA FOR SPEAKING ACTIVITIES BASED ON TASK-BASED LEARNING *Astry Iswara Kelana Citra **Dr. Anni Holila Pulungan, M.Hum. **Maya Oktora, S.Pd., M.Hum. ABSTRACT Astry Iswara Kelana Citra 2152121005 Citra, Astry Iswara Kelana. Registration Number: 2152121005. Developing English Digital Conversation Media for Speaking Activities Based on Task Based Learning. A Thesis. English Educational Program, State University of Medan, 2020. This research was aimed to develop English digital conversation media for speaking activities based on the students’ need at SMAN 1 Kec. Binjai Kab.Langkat. This research was conducted by using Research and Development (R&D) method. There were seven steps applied in this research, the steps were: 1). Potential and Problem 2). Gathering data and information 3). Product design 4). Validating to experts 5). Revising Design 6). Product test 7). Final product revision. The subject of this research was tenth grade students of social science at SMAN 1 Kec. Binjai Kab. Langkat. The instruments of collecting data were questionnaires and interview. The data analyzed by using descriptive technique. Need analysis questionnaire was calculated using percentage by Suharto (2006) to get an information of students’ need before developing digital conversation media. Expert judgment data were calculated by using Likert Scale, mean and criteria interval of expert judgment to know the validity of digital conversation media which has been develop. The result of expert validation was 4,5 which mean English conversation media is Very Good category. Therefore the media is appropriate to use in the tenth grade students of SMA N 1 Kec.Binjai Kab.Langkat to teach speaking. Keywords: Research and Development, Digital Conversation Media, Task Based Learning.